Divergência genética entre genótipos de algodoeiro (Gossypium hirsutum L.) estimada por análise de marcadores RAPD - Cabral, Terezinha Aparecida Teixeira (1997)
Knowledge of genetic distances between individuals or populations in a breeding program can complement phenotypic information by helping to select individuals for hybridization and to obtain segregating populations with greater variability. The RAPD technique that detects nucleotide sequence polymorphisms based on DNA amplification using as an primer an arbitrary sequence oligonucleotide ("primer") has advantages that make it suitable for routine use in genetic relatedness studies. The objectives of this work were: to identify primers that generate polymorphisms among cotton genotypes (Gossypium HrMm L), to compare the effect of primer size on polymorphism determination, to determine genetic distances between 24 cotton genotypes from 8 countries using the random amplified polymorphic DNA (RAPD) technique and compare with results obtained by the phenolic analysis of these 24 genotypes based on the evaluation of 52 qualitative and quantitative traits using numerical taxonomy. The 24 genotypes were evaluated by the RAPD technique using short primers and long primer combinations. A matrix was assembled according to the presence (1) and absence (0) of bands, the distances calculated by the disagreement percentages, Nei and Li complements and Jacard distances, and the UPGMA grouping. Short primers generated polymorphic bands that were efficient in differentiating genotypes, while long primers failed to show differences between genotypes. Comparing the three methods for calculating genetic distance, the method that best correlated with the distances obtained in the phenotypic character analysis was the disagreement percentage, which agreed in 93% with Jacard's distance and 91% with the complement of Nei and Li. The maximum percentage disagreement between genotypes based on the polymorphisms generated by short primers was 18%, possibly indicating a genetic base not as broad as revealed by phenotypic characters. The correlation between phenotypic analysis and short primer analysis was moderate and negative (r = -0.43).